Estimating ocean heat content from the ocean thermal expansion parameters using satellite data - V. P. Kondeti; S. Palanisamy (Earth System Dynamics)
Ocean heat content (OHC) is a depth-integrated physical oceanographic variable used to precisely measure ocean warming. Because of the limitations associated with in situ conductivity, temperature, and depth (CTD) data as well as ocean reanalysis system products, satellite-based approaches have gained importance in estimating the daily to decadal variability of OHC over the vast oceanic region. Efforts to minimize the biases in satellite-based OHC estimates are needed to realize the actual response of the ocean to the brunt of climate change. In the current study, an attempt has been made to better implement the satellite-based ocean thermal expansion method to estimate OHC at 17 depth extents ranging from the surface to 700 m. To achieve this objective, artificial neural network (ANN) models were developed to derive thermosteric sea level (TSL) from a given dataset of sea surface temperature, sea surface salinity, geographical coordinates, and climatological TSL. The model-derived TSL data were further used to estimate OHC changes based on the thermal expansion efficiency of heat. Statistical analysis showed high correlation coefficients and low errors in the validation of model-derived TSL and OHC for the 700 m modeling depth (N 388 469, R 0.9926 and 0.9922, RMSE 1.16 m and 1.56 GJ m−2, MBE −0.19 m and −0.24 GJ m−2, MBPE −0.46 % and −0.03 %, MAE 0.76 m and 1.03 GJ m−2, and MAPE 2.34 % and 0.13 %) and nearly similar results at the remaining modeling depths. These results suggest that the proposed ANN models are capable of generating satellite-based daily OHC maps by covering both shallower and deeper oceanic regions of varying bathymetry levels (≥20 m). In addition, the first-ever attempt to estimate the ocean thermal expansion component (i.e., TSL) from satellite data was successful, and the model-derived TSL can be used to obtain high-end sea level rise products in the global ocean.